THE NISA'UL MA'HAD COACHING MODEL AS AN EFFORT TO EMPOWER FEMALE STUDENTS AT MODERN ISLAMIC BOARDING SCHOOL AL-ISTIQAMAH NGATABARU: Coaching Model; Nisa'ul Ma'had; Empowerment of Female Students - Eka Selvi Anggitasari Anggi; Jumri Hi, Tahang Basire; Fatima (SOSIOEDUKASI, 2026)
This study examines the Nisa'ul Ma'had coaching model as an effort to empower female students (santriwati) at Modern Islamic Boarding School Al-Istiqamah Ngatabaru, while analyzing its implications for enhancing their capacity and empowerment. A qualitative approach with a case study design was employed, utilizing in-depth interviews, participatory observation, and documentation, analyzed through the interactive model of Miles, Huberman, and Saldaña, and validated via source and method triangulation. The findings reveal that the Nisa'ul Ma'had program emerged from the organic initiative of female teachers (ustadzah), driven by social capital in the form of trust, shared ownership, and women's solidarity, rather than formal bureaucratic planning. The program operates through three mutually reinforcing pillars: an intergenerational gathering forum, domestic skill competitions, and thematic women's empowerment seminars, all managed in a collegial, flexible, yet consistent manner. The program demonstrably improved santriwati's capacity, strengthened institutional cohesion, and cultivated collaborative leadership and value-based independence. This study produces a new finding that both enriches and corrects the theoretical assumption that successful women's empowerment requires complex systemic prerequisites. A program grounded in social capital and pesantren cultural values is proven effective and sustainable, contributing directly to SDGs Goal 4 on quality education and Goal 5 on gender equality and women's empowerment.